Cocatalyst / heterostructure / tungsten trioxide photo-anode integrated structure and preparation method and application thereof
By building zinc oxide/tungsten tungsten heterogeneous structures on the anode of tungsten oxide anode and loading precious metal modified nickelized nickelized catalysts, the problem of poor stability and product types in the process of optical catalytic glycerin oxidation has been solved, and it has achieved high efficiency, Stable glycerin oxidation, single product types and high added value.
Patent Information
- Application Number
- CN202411482508.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The existing tungsten trioxide photoanode has poor stability and many kinds of products during the photoelectric catalytic glycerol oxidation process, resulting in poor catalytic performance.
By constructing nickelized nickelized catalysts with zinc oxide/tungsten albumrobia and loading precious metals modified, inhibit the composite of photocagenic carriers, accelerate the migration and surface response of photogenic charge, and improve the stability of the reaction and the added value of the product.
It significantly improves the performance of photoelectric catalytic glycerin oxidation, including improving the density of light current and incident photons-current conversion efficiency, extending the life of photocopy charge, and only two types of C3 products: glycerin and 1,3-dihydroxylthone. The efficiency is as high as 82.9%.
Smart Images

Figure CN119352085A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomass conversion and photoelectrocatalysis, and specifically relates to a co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure and a preparation method and application thereof. Background Art
[0002] Since the 1970s, the human economy has entered a stage of rapid development, and global carbon emissions have also increased year by year, leading to the continuous intensification of the greenhouse effect. Faced with increasingly serious climate change, countries around the world have introduced energy-saving and emission reduction plans to reduce carbon emissions.
[0003] Among many new energy sources, solar energy is favored by people because of its high energy density, wide application range and low cost. Photoelectric catalysis is developed based on this. It is a new type of catalysis and is widely used. Secondly, biomass is a low-carbon fuel. Its carbon comes from the atmosphere and returns to the atmosphere after a series of cycles. In 2004, the U.S. Department of Energy announced twelve biomass-based platform compounds. These compounds can be converted from biomass such as lignocellulose and can be further converted into high-value-added chemicals, with great utilization potential. Glycerol is one of the twelve biomass-based platform compounds, and it is a by-product of biodiesel. 10%wt of glycerol can be obtained by producing 1kg of biodiesel. Therefore, it has overcapacity and low price, but it can be further converted into a series of high-value-added chemicals such as glyceraldehyde and 1,3-dihydroxyacetone, which has great utilization value.
[0004] The use of photoelectrocatalysis for biomass conversion can not only make the reaction conditions milder and reduce energy consumption, but also convert cheap biomass into high-value-added chemicals, thereby replacing the low-value-added oxygen at the anode end of traditional photoelectrocatalytic water splitting. While increasing the added value of the anode end product, coupling with the cathode to produce hydrogen is an effective way to develop clean energy and fine chemicals.
[0005] According to the principle of band structure, heterostructures can inhibit the recombination of photogenerated carriers inside the photoelectrode and accelerate their migration rate; surface co-catalysts can increase the surface reaction rate and improve the ability of photogenerated electrons or holes to react with chemical substances in the solution. Zhang Fuqin et al. constructed an integrated system of Bi / BiVO4 / WO3, in which BiVO4 and WO3 form a heterostructure, and Bi is used as a surface co-catalyst. The selectivity of 1,3-dihydroxyacetone reaches 60% (Feng X., Feng X, Zhang F. Journal of Materials Chemistry A, 2023, 11(37): 20242-20253), but it still has the disadvantages of poor stability and a large number of product types. Summary of the invention
[0006] In order to improve the performance of photoelectrocatalytic glycerol oxidation by tungsten trioxide photoanode, the present invention proposes a co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure and its preparation method and application, which inhibits the recombination of photogenerated carriers by constructing heterostructures and loading surface co-catalysts, accelerates their migration rate, increases the life of photogenerated charges, and reduces the energy barrier of surface reactions, improves the stability of reactions, thereby improving the performance of photoelectrocatalytic glycerol oxidation. In the present invention, zinc oxide is used as an intermediate layer to inhibit the recombination of photogenerated carriers; while precious metals have good conductivity and catalytic activity, and the co-catalyst modified with precious metals greatly reduces the surface energy barrier, improves the surface reaction kinetics, and prolongs the life of photogenerated charges. At the same time, there are only two C3 products, glyceraldehyde and 1,3-dihydroxyacetone, in the system, and the types are relatively small, which provides a feasible path for improving the high-value coupled hydrogen production of photoelectrocatalytic biomass.
[0007] In order to achieve the above objectives, the present invention adopts the following technical solutions:
[0008] A method for preparing a co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure, the preparation method comprising the following steps:
[0009] Step 1: pretreat the conductive substrate, and then prepare a tungsten trioxide photoanode on the conductive substrate.
[0010] Step 2: Mix zinc acetate, ethanolamine and anhydrous ethanol in a certain proportion, hydrothermally obtain a zinc oxide precursor solution, and then spin-coat it on the surface of the tungsten trioxide photoanode prepared in step 1. Finally, use a muffle furnace to anneal in air to obtain a zinc oxide / tungsten trioxide heterostructure.
[0011] Step 3, after grinding and mixing sodium hypophosphite, noble metal hydrated chloride salt and nickel chloride hexahydrate in a certain proportion, placing the mixture in a tubular furnace, calcining under an argon atmosphere, cooling the obtained solid product to room temperature, washing, centrifuging and drying, to obtain a noble metal-modified nickel phosphide co-catalyst.
[0012] Step 4, dispersing the noble metal-modified nickel phosphide co-catalyst obtained in step 3 in anhydrous ethanol by ultrasonication to obtain a suspension; spin-coating the obtained suspension on the surface of the zinc oxide / tungsten trioxide heterostructure prepared in step 2, and finally annealing in air to obtain a co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure.
[0013] Furthermore, in step 1, the conductive substrate is fluorine-doped tin dioxide conductive glass or tin-doped indium oxide film.
[0014] Furthermore, the pretreatment process in step 1 is: placing the conductive substrate in deionized water, acetone and ethanol in turn and ultrasonicating for 30 to 60 minutes respectively, then drying at 40 to 60° C. for 3 to 4 hours, and finally treating in an ozone atmosphere for 10 to 40 minutes.
[0015] Furthermore, in the step 1, a tungsten trioxide photoanode is prepared by a hydrothermal method: 0.3-0.6 g of ammonium metatungstate and 3-6 mL of 6.25 M concentrated hydrochloric acid are added to every 30-60 mL of deionized water, stirred for 10-20 min, and then 0.75-1.25 mL of hydrogen peroxide is added, and stirring is continued for 0.5-2 h to obtain a precursor solution; then the pretreated conductive substrate is placed in a polytetrafluoroethylene-lined kettle with the conductive surface facing downward, 20-30 mL of the precursor solution is added, and then hydrothermal treatment is performed at 140-180° C. for 3-5 h, and then the substrate is taken out after cooling to room temperature, and the solid impurities on the tungsten trioxide photoanode are cleaned with deionized water and ethanol and dried for 10-20 min, and then placed in a muffle furnace, and annealed at 400-500° C. in an air atmosphere for 2-3 h to obtain a tungsten trioxide photoanode.
[0016] Furthermore, the step 2 is specifically as follows: 40 to 80 μL of ethanolamine and 0.15 to 0.25 mol of zinc acetate are added to every 5 to 10 mL of ethanol, and after mixing, a zinc oxide precursor solution is obtained by hydrothermal treatment at 50 to 80° C. for 3 to 6 hours, and the obtained zinc oxide precursor solution is spin-coated onto the tungsten trioxide photoanode in step 1, with a spin-coating speed of 1500 to 2000 rpm, and a spin-coating amount of 0.2 to 0.4 mL per 1 cm×2 cm area of the photoanode, and then placed in a muffle furnace for annealing in air, with an annealing temperature of 350 to 500° C. and an annealing time of 10 to 40 min to obtain a zinc oxide / tungsten trioxide heterostructure.
[0017] Furthermore, in step 3, the molar ratio of the noble metal hydrated chloride salt, nickel chloride hexahydrate and sodium hypophosphite is (0.5-2):10:50, the calcination temperature is 200-400° C., and the time is 1-4 hours, wherein the noble metal hydrated chloride salt is selected from one of tetrachloroauric acid trihydrate, chloroplatinic acid hexahydrate and potassium chloropalladate.
[0018] Furthermore, in step 4, the mass concentration of the noble metal-modified nickel phosphide promoter in the suspension is 1.0-5.0 mg / mL, the spin coating speed is 1000-1500 rpm, the spin coating amount on each 1 cm×2 cm area of the photoanode is 0.1-0.5 mL, the annealing temperature is 100-160° C., and the time is 1-4 h.
[0019] A co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure is prepared based on the above preparation method, wherein the synthesized tungsten trioxide photoanode is a nanorod structure, zinc oxide is a thin layer structure covering the surface of tungsten trioxide, and the co-catalyst modified by precious metals is nanoparticles uniformly dispersed on the surface of the heterostructure.
[0020] An application of a co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure, which is applied to photoelectrocatalytic glycerol high-value coupled hydrogen production. Specifically, the prepared co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure is used as the working electrode, platinum wire is used as the counter electrode, and Ag / AgCl is used as the reference electrode to form a standard three-electrode reaction system; the reaction electrolyte is a mixed aqueous solution of 0.5M sodium sulfate and 0.01-1M glycerol, and the reaction is carried out under a simulated solar light source (300W xenon lamp, light intensity of 100mW / cm 2 ) conditions, the products at the anode were 1,3-dihydroxyacetone and glyceraldehyde, and the products at the cathode were hydrogen.
[0021] The principle of the present invention is that precious metals are widely used in thermal catalysis and electrocatalysis, but are less used in the field of photoelectrocatalysis. They have good conductivity and catalytic activity, can accelerate the migration of photogenerated carriers, and improve surface reaction kinetics. In the photoelectrocatalytic glycerol oxidation system, when light irradiates the tungsten trioxide photoanode, it absorbs photons equal to or greater than its band gap energy, thereby causing the internal photogenerated carriers to separate into electrons and holes. The electrons migrate to the surface of the counter electrode through the external circuit to react and produce hydrogen, and the holes react with the glycerol adsorbed on the surface of the photoanode to produce two products, glyceraldehyde and 1,3-dihydroxyacetone. However, for the tungsten trioxide photoanode body, the internal electrons and holes recombine severely, which results in only a few holes and electrons being able to undergo glycerol oxidation and hydrogen evolution reactions. In the present invention, the co-catalyst / heterostructure / tungsten trioxide integrated structure serves as a photoanode, the heterostructure of zinc oxide and tungsten trioxide can inhibit the recombination of photogenerated carriers, and the co-catalyst modified with a noble metal can reduce the interface resistance between the heterostructure and the electrolyte, accelerate the migration of photogenerated holes, and increase the rate of the surface reaction, so that it can obtain excellent photoelectrocatalytic glycerol oxidation performance.
[0022] Compared with the prior art, the present invention has at least the following advantages:
[0023] (1) Due to the synergistic effect of the noble metal-doped co-catalyst and the intermediate layer, the separation of photogenerated carriers is suppressed, the surface reaction energy barrier is reduced, the surface reaction kinetics is improved, and the reaction rate of photogenerated holes and glycerol is promoted. As a result, the integrated photoanode system exhibits relatively excellent glycerol oxidation performance, with a photocurrent density of 3.15 mA / cm at 1.23 V relative to the reversible hydrogen electrode. 2, and the incident photon-current conversion efficiency is increased to 57.4%, and it can operate stably for more than 50 hours. Its catalytic performance and stability are significantly better than those of the single tungsten trioxide photoanode.
[0024] (2) For the glycerol oxidation reaction, the present invention only has two C3 products, glyceraldehyde and 1,3-dihydroxyacetone, and the total Faraday efficiency is as high as 82.9%. The integrated structure preparation method of the present invention has simple process conditions, which is easy to explore the preparation of large-scale electrodes in the future, and provides a feasible path for the high-value coupling of photoelectrocatalytic biomass to produce hydrogen. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 X-ray diffraction spectra (XRD) of the tungsten trioxide photoanode, zinc oxide / tungsten trioxide heterostructure, and gold-modified nickel phosphide / zinc oxide / tungsten oxide photoanode integrated structure materials prepared in Example 1.
[0026] Figure 2 This is the X-ray diffraction spectrum (XRD) of the gold-modified nickel phosphide co-catalyst prepared in Example 1.
[0027] Figure 3 This is a scanning electron microscope image (SEM) of the nanorod-shaped tungsten trioxide photoanode prepared in Example 1.
[0028] Figure 4 This is a scanning electron microscope image (SEM) of the zinc oxide / tungsten trioxide heterostructure prepared in Example 1.
[0029] Figure 5 This is a scanning electron microscope image (SEM) of the gold-modified nickel phosphide co-catalyst prepared in Example 1.
[0030] Figure 6 This is a scanning electron microscope (SEM) image of the gold-modified nickel phosphide / zinc oxide / tungsten trioxide photoanode integrated structure prepared in Example 1.
[0031] Figure 7 Linear sweep voltammograms (LSV) of the tungsten trioxide photoanode, zinc oxide / tungsten trioxide heterostructure, and gold-modified nickel phosphide / zinc oxide / tungsten oxide photoanode integrated structure prepared in Example 1 in a sodium sulfate electrolyte containing glycerol.
[0032] Figure 8 Linear sweep voltammograms (LSV) of the photoanodes prepared in Example 1 and Comparative Example 1 in sodium sulfate electrolyte containing glycerol.
[0033] Fig. 9This is a product distribution diagram of the photoelectrocatalytic glycerol oxidation of the gold-modified nickel phosphide / zinc oxide / tungsten trioxide photoanode integrated structure prepared in Example 1. In the figure, the bar graph is the production rate and the dotted line graph is the Faraday efficiency. DETAILED DESCRIPTION
[0034] Example 1
[0035] A method for preparing a co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure comprises the following steps:
[0036] Step 1: 2 cm × 3 cm fluorine-doped tin dioxide conductive glass (FTO) was ultrasonicated in deionized water, acetone and anhydrous ethanol for 45 min, then dried in an oven at 60 ° C for 3 h, and then treated under ozone for 20 min. Tungsten trioxide photoanode was prepared on FTO using a hydrothermal method. Specifically: add 0.6g of ammonium metatungstate to 60mL of deionized water, add 6mL of 6.25M concentrated hydrochloric acid, stir for 20min, add 1.25mL of hydrogen peroxide, and stir for 2h to obtain a tungsten trioxide precursor solution; then place the treated FTO in a polytetrafluoroethylene-lined reactor with its face down, add 30mL of tungsten trioxide precursor solution, put it in an oven and hydroheat it at 180℃ for 5h, wait for the reaction to end and cool to room temperature before taking it out, clean the solid impurities on the photoanode with deionized water and ethanol, dry it for 10min, put it in a muffle furnace and calcine it at 500℃ for 3h in an air atmosphere to obtain a nanorod-shaped tungsten trioxide photoanode. Figure 3 This is a scanning electron microscope (SEM) image of the tungsten trioxide photoanode. It can be seen that the synthesized tungsten trioxide photoanode is a nanorod-like structure.
[0037] Step 2, using a hydrothermal method to prepare a zinc oxide precursor solution, specifically: 5mL of ethanol, 40μL of ethanolamine and 0.25mol of zinc acetate are uniformly mixed, and hydrothermal treatment is performed at 50°C for 3h to obtain a zinc oxide precursor solution. The zinc oxide precursor solution is spin-coated onto the tungsten trioxide photoanode prepared in step 1, with a spin coating amount of 0.4mL and a rotation speed of 1500rmp, and then placed in a muffle furnace and annealed at 350°C for 10min in air to obtain a zinc oxide / tungsten trioxide heterostructure. Figure 4 This is a scanning electron microscope (SEM) image of the ZnO / WTO heterostructure.
[0038] Step 3, using phosphating to prepare a gold-modified nickel phosphide promoter, trihydrate tetrachloroauric acid, hexahydrate nickel chloride and sodium hypophosphite in a molar ratio of 1:10:50 are fully mixed and ground evenly, the ground solid is placed in an argon furnace and calcined at 250° C. for 2 h, after the reaction is completed and cooled to room temperature, the solid powder is washed with deionized water and anhydrous ethanol, centrifuged and dried to obtain a gold-modified nickel phosphide promoter, Figure 5 The scanning electron microscope (SEM) image of the prepared gold-modified nickel phosphide co-catalyst is shown in FIG. Figure 2 From the XRD pattern of the co-catalyst, it was found that the synthesized Au (PDF#04-0784) was a single substance, and the 2θ positions of 40.80°, 44.60° and 47.31° were the (111), (201) and (210) crystal planes of Ni2P (PDF#03-0953), respectively.
[0039] Step 4, dispersing the gold-modified nickel phosphide co-catalyst powder prepared in step 3 in anhydrous ethanol at 3 mg / mL, spin-coating it onto the zinc oxide / tungsten trioxide photoanode prepared in step 2, with a spin coating amount of 0.4 mL and a rotation speed of 1200 rpm, and then annealing it in a muffle furnace at 120° C. in air for 2 hours to obtain a gold-modified nickel phosphide / zinc oxide / tungsten trioxide photoanode integrated structure, Figure 6 This is a scanning electron microscope (SEM) image of the prepared gold-modified nickel phosphide / zinc oxide / tungsten trioxide photoanode. It can be seen that the co-catalyst is nanoparticles uniformly dispersed on the surface of the heterogeneous structure.
[0040] Example 2
[0041] Step 1: Place a 1cm×2cm tin-doped indium oxide film (ITO) in deionized water, acetone and ethanol for ultrasonic treatment for 30 minutes, then dry it in an oven at 50°C for 3.5 hours, and treat it under ozone conditions for 10 minutes after drying. Prepare a tungsten trioxide photoanode on ITO using a hydrothermal method. Specifically: add 0.4g of ammonium metatungstate to 30mL of deionized water, add 4mL of 6.25M concentrated hydrochloric acid, stir for 10 minutes, add 1mL of hydrogen peroxide, and stir for another 30 minutes to obtain a tungsten trioxide precursor solution. Then place the treated ITO in a polytetrafluoroethylene-lined reactor with the front side facing down, add 20mL of the precursor solution, put it in an oven and hydrothermally heat it at 140°C for 3 hours, wait for the reaction to end and cool it to room temperature, then take it out, clean the solid impurities on the photoanode with deionized water and ethanol, dry it for 15 minutes, and then put it in a muffle furnace in an air atmosphere and calcine it at 400°C for 2 hours to obtain a tungsten trioxide photoanode.
[0042] Step 2, using a hydrothermal method to prepare a zinc oxide precursor solution, specifically: 10mL of ethanol, 60μL of ethanolamine and 0.15mol of zinc acetate are uniformly mixed, and hydrothermal treatment is performed at 70°C for 4h to obtain a zinc oxide precursor solution. The zinc oxide precursor solution is spin-coated onto the tungsten trioxide photoanode prepared in step 1, with a spin coating amount of 0.2mL and a rotation speed of 1700rmp, and then placed in a muffle furnace for annealing at 400°C for 20min under air conditions to obtain a zinc oxide / tungsten trioxide heterostructure.
[0043] Step 3, using the phosphating method to prepare a palladium-modified nickel phosphide co-catalyst, potassium chloropalladate, nickel chloride hexahydrate and sodium hypophosphite in a molar ratio of 0.5:10:50 are fully mixed and ground evenly, and the ground solid is placed in an argon furnace and calcined at 200°C for 1 hour. After the reaction is completed and cooled to room temperature, the solid powder is washed with deionized water and anhydrous ethanol, centrifuged and dried to obtain a palladium-modified nickel phosphide co-catalyst.
[0044] Step 4, disperse the palladium-modified nickel phosphide co-catalyst powder prepared in step 3 in anhydrous ethanol at 1 mg / mL, and spin-coat it on the zinc oxide / tungsten trioxide photoanode prepared in step 2, with a spin coating amount of 0.1 mL and a rotation speed of 1000 rpm. Then, anneal it at 100°C in air in a muffle furnace for 4 hours to obtain a palladium-modified nickel phosphide / zinc oxide / tungsten trioxide photoanode integrated structure.
[0045] Example 3
[0046] Step 1: Place 1cm×2cm ITO in deionized water, acetone and ethanol for 60 minutes, then dry it in an oven at 40℃ for 4 hours, and treat it under ozone conditions for 40 minutes after drying. Prepare tungsten trioxide photoanode on ITO using hydrothermal method. Specifically: add 0.3g ammonium metatungstate to 50mL deionized water, add 3mL 6.25M concentrated hydrochloric acid, stir for 15 minutes, add 0.75mL hydrogen peroxide, and stir for 1 hour to obtain tungsten trioxide precursor solution. Then place the treated ITO in a polytetrafluoroethylene-lined reactor with the face down, add 25mL precursor solution, put it in an oven and hydrothermally heat it at 170℃ for 4 hours, cool it to room temperature after the reaction is completed, take it out, clean the solid impurities on the photoanode with deionized water and ethanol, dry it for 20 minutes, put it in a muffle furnace and calcine it at 450℃ for 2.5 hours in an air atmosphere to obtain a tungsten trioxide photoanode.
[0047] Step 2, using a hydrothermal method to prepare a zinc oxide precursor solution, specifically: 7 mL of ethanol, 80 μL of ethanolamine and 0.2 mol of zinc acetate are uniformly mixed, and hydrothermal treatment is performed at 80°C for 6 hours to obtain a zinc oxide precursor solution. The zinc oxide precursor solution is spin-coated onto the tungsten trioxide photoanode prepared in step 1, with a spin coating amount of 0.4 mL and a rotation speed of 2000 rpm, and then placed in a muffle furnace for annealing at 500°C for 40 minutes under air conditions to obtain a zinc oxide / tungsten trioxide heterostructure.
[0048] Step 3, using the phosphating method to prepare a platinum-modified nickel phosphide co-catalyst, fully mix hexahydrate chloroplatinic acid, hexahydrate nickel chloride and sodium hypophosphite in a molar ratio of 2:10:50 and grind them evenly, put the ground solid into an argon furnace and calcine at 400°C for 4 hours, after the reaction is completed and cooled to room temperature, the solid powder is washed with deionized water and anhydrous ethanol, centrifuged and dried to obtain a platinum-modified nickel phosphide co-catalyst.
[0049] Step 4, disperse the platinum-modified nickel phosphide co-catalyst powder prepared in step 3 in anhydrous ethanol at 5 mg / mL, and spin-coat it on the zinc oxide / tungsten trioxide photoanode prepared in step 2, with a spin coating amount of 0.5 mL and a rotation speed of 1500 rpm. Then, anneal it in a muffle furnace at 160°C under air conditions for 1 hour to obtain a platinum-modified nickel phosphide / zinc oxide / tungsten trioxide photoanode system.
[0050] Comparative Example 1
[0051] After preparing the zinc oxide / tungsten trioxide heterostructure according to steps 1 and 2 in Example 1, a nickel phosphide / zinc oxide / tungsten trioxide photoanode system was prepared according to the following steps:
[0052] Step 3, prepare the nickel phosphide co-catalyst by phosphating, mix nickel chloride hexahydrate and sodium hypophosphite in a molar ratio of 1:5 thoroughly and grind them evenly, put the ground solid into an argon furnace and calcine at 250° C. for 2 hours, wait for the reaction to be completed and cool to room temperature, wash the solid powder with deionized water and anhydrous ethanol, centrifuge and dry to obtain the nickel phosphide co-catalyst.
[0053] Step 4, disperse the nickel phosphide co-catalyst powder prepared in step 3 in anhydrous ethanol at 3 mg / mL, and spin-coat it on the prepared zinc oxide / tungsten trioxide photoanode with a spin coating amount of 0.4 mL and a rotation speed of 1200 rpm. Then, anneal it at 120°C in a muffle furnace under air conditions for 2 hours to obtain a nickel phosphide / zinc oxide / tungsten trioxide photoanode system.
[0054] Figure 1The XRD images of the tungsten trioxide photoanode, zinc oxide / tungsten trioxide heterostructure, and gold-modified nickel phosphide / zinc oxide / tungsten oxide photoanode integrated structure prepared in Example 1 are shown in Figure 1. The synthesized tungsten trioxide photoanode is a monoclinic phase (PDF#72-0677) and has three obvious characteristic peaks at 2θ of 23.11°, 23.58°, and 24.35°, respectively, belonging to the (002), (020), and (200) crystal planes. With the addition of the intermediate layer and the co-catalyst, the XRD image has almost no change, which we believe is due to the low loading amount. Although XRD cannot show the loading of various layers, combined with Figure 3-6 It was demonstrated that the integrated photoanode system was successfully synthesized.
[0055] Figure 7 The linear sweep voltammogram of the tungsten trioxide photoanode, zinc oxide / tungsten trioxide heterostructure, and gold-modified nickel phosphide / zinc oxide / tungsten oxide photoanode integrated structure prepared in Example 1 in a sodium sulfate electrolyte containing glycerol. It can be seen from the figure that the photocurrent density of the gold-modified nickel phosphide / zinc oxide / tungsten trioxide photoanode integrated structure at 1.23V relative to the reversible hydrogen electrode is 3.15mA / cm 2 , higher than 2.08mA / cm of tungsten trioxide 2 and 2.26mA / cm for zinc oxide / tungsten trioxide 2 ; This shows that the co-catalyst reduces the surface resistance and improves the performance of glycerol oxidation. Figure 8 The linear sweep voltammograms of the gold-modified nickel phosphide / zinc oxide / tungsten oxide photoanode integrated structure prepared in Example 1 and the nickel phosphide / zinc oxide / tungsten trioxide photoanode system prepared in the comparative example in a sodium sulfate electrolyte containing glycerol show that the photocurrent density of nickel phosphide / zinc oxide / tungsten trioxide at 1.23 V relative to the reversible hydrogen electrode is only 2.52 mA / cm 2 This is because the noble metal doping improves the conductivity of the co-catalyst. At the same time, the noble metal is also part of the active center and its activity is higher than that of nickel phosphide. Therefore, after the noble metal is doped, the surface resistance is further reduced, the surface reaction kinetics are improved, the efficiency of charge transfer is accelerated, and the activity of photoelectrocatalytic glycerol oxidation is improved.
[0056] Fig. 9 The gold-modified nickel phosphide / zinc oxide / tungsten trioxide photoanode integrated structure prepared in Example 1 was exposed to a simulated solar light source (300W xenon lamp with a light intensity of 100mW / cm 2 ) conditions, and the product was analyzed by high performance liquid chromatography after the reaction. The reaction system was exposed to a simulated solar light source (300W xenon lamp, light intensity of 100mW / cm 2) under the conditions of 0.8 V relative to the reversible hydrogen electrode and 1 M glycerol, after 2 h of reaction, for the glycerol oxidation reaction, there were almost no other products except 1,3-dihydroxyacetone and glyceraldehyde, and the total Faradaic efficiency reached 82.9%, and the glycerol consumption rate reached 191.4 mmol / (m 2 h). And with the increase of voltage, its total Faradaic efficiency continues to decrease, indicating that the closer the voltage is to the theoretical potential of oxygen production, the higher the competitiveness of water oxidation is. However, even if the voltage is increased, glycerol oxidation still occupies a dominant position in this system.
[0057] The above-mentioned embodiments only express the implementation methods of the present invention, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing a co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure, characterized in that: The preparation method first synthesizes a zinc oxide / tungsten trioxide heterostructure; secondly, synthesizes a noble metal-modified nickel phosphide co-catalyst through phosphating; finally, loads it on the surface of the heterostructure to successfully construct an integrated system of co-catalyst / heterostructure / photoanode.
2. The method for preparing a co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure according to claim 1, characterized in that: The preparation method comprises the following steps: Step 1, pretreating a conductive substrate and preparing a tungsten trioxide photoanode on the conductive substrate; Step 2, synthesizing a zinc oxide / tungsten trioxide heterostructure on a conductive substrate by spin coating and calcination; Zinc acetate, ethanolamine and anhydrous ethanol are mixed in a certain proportion, and then hydrothermally prepared to obtain a zinc oxide precursor solution, which is then spin-coated on the surface of the tungsten trioxide photoanode prepared in step 1, and annealed in air to obtain a zinc oxide / tungsten trioxide heterostructure; Step 3, grinding and mixing sodium hypophosphite, noble metal hydrated chloride salt and nickel chloride hexahydrate in a certain proportion, placing the mixture in a tube furnace, calcining under an argon atmosphere, cooling the obtained solid product to room temperature, washing, centrifuging and drying to obtain a noble metal-modified nickel phosphide promoter; Step 4, dispersing the noble metal-modified nickel phosphide co-catalyst obtained in step 3 in anhydrous ethanol by ultrasonication to obtain a suspension; spin-coating the obtained suspension on the surface of the zinc oxide / tungsten trioxide heterostructure prepared in step 2, and finally annealing in air to obtain a co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure.
3. The method for preparing a co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure according to claim 1, characterized in that: In the step 1, the conductive substrate is fluorine-doped tin dioxide conductive glass or tin-doped indium oxide film; in the step 3, the noble metal hydrated chloride salt is selected from one of tetrachloroauric acid trihydrate, chloroplatinic acid hexahydrate and potassium chloropalladate.
4. The method for preparing a co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure according to claim 1, characterized in that: In the step 1, a tungsten trioxide photoanode is prepared on a conductive substrate using a hydrothermal method, specifically: Add 0.3-0.6 g of ammonium metatungstate and 3-6 mL of 6.25 M concentrated hydrochloric acid to every 30-60 mL of deionized water, stir evenly, then add 0.75-1.25 mL of hydrogen peroxide, continue stirring for 0.5-2 h, and obtain a precursor solution; Subsequently, the pretreated conductive substrate is placed in a polytetrafluoroethylene-lined kettle with the conductive surface facing downward, and after adding 20-30 mL of the precursor solution, it is hydroheated at 140-180° C. for 3-5 hours. After cooling to room temperature, it is taken out, cleaned and dried, and then placed in a muffle furnace and annealed at 400-500° C. for 2-3 hours in an air atmosphere to obtain a tungsten trioxide photoanode.
5. The method for preparing a co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure according to claim 1, characterized in that: The step 2 is specifically as follows: Add 40-80 μL of ethanolamine and 0.15-0.25 mol of zinc acetate to every 5-10 mL of ethanol, mix, and hydrothermally heat at 50-80° C. for 3-6 hours to obtain a zinc oxide precursor solution. Spin-coat the zinc oxide precursor solution onto the tungsten trioxide photoanode prepared in step 1, with a spin coating amount of 0.2-0.4 mL per 1 cm×2 cm area of the photoanode. Then put it into a muffle furnace for annealing in air at a temperature of 350-500° C. for 10-40 minutes to obtain a zinc oxide / tungsten trioxide heterostructure.
6. The method for preparing a co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure according to claim 1, characterized in that: In the step 3, the molar ratio of the noble metal hydrated chloride salt, nickel chloride hexahydrate and sodium hypophosphite is (0.5-2):10:50, the calcination temperature is 200-400° C., and the calcination time is 1-4 hours.
7. The method for preparing a co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure according to claim 1, characterized in that: In the step 4, the mass concentration of the noble metal-modified nickel phosphide promoter in the suspension is 1.0-5.0 mg / mL, the spin coating amount on the photoanode per 1 cm×2 cm area is 0.1-0.5 mL, the annealing temperature is 100-160° C., and the time is 1-4 h.
8. A co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure, characterized in that: The co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure is prepared based on the preparation method described in any one of claims 1-7, wherein the synthesized tungsten trioxide photoanode is a nanorod-like structure, zinc oxide is a thin layer structure covering the surface of tungsten trioxide, and the co-catalyst modified with precious metals is nanoparticles uniformly dispersed on the surface of the heterostructure.
9. The use of a co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure according to claim 8, characterized in that: The co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure is applied to photoelectrocatalytic glycerol high-value coupled hydrogen production.
10. The use of a co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure according to claim 9, characterized in that: A standard three-electrode reaction system was composed of a co-catalyst / heterostructure / tungsten trioxide photoanode integrated structure as the working electrode, a platinum wire as the counter electrode, and Ag / AgCl as the reference electrode; the reaction electrolyte was a mixed aqueous solution of 0.5 M sodium sulfate and 0.01-1 M glycerol, and the photoelectrocatalytic glycerol oxidation reaction was carried out under simulated solar light conditions.
Citation Information
Patent Citations
Novel carbon-doped tungsten trioxide and zinc ferrite heterojunction photoelectrocatalysis anode material and preparation method thereof
CN115216802A
Gold and platinum double-metal modified tungsten trioxide photo-anode as well as preparation method and application of gold and platinum double-metal modified tungsten trioxide photo-anode
CN115717249A
Composite iron oxide photo-anode coupled with multifunctional layer, preparation method and application of composite iron oxide photo-anode
CN117987850A
Transition metal phosphide composite tungsten trioxide photo-anode as well as preparation method and application thereof
CN118326447A
Cited By
S-type WO3 / FeWO4 heterojunction photocatalyst as well as synthesis method and application method thereof
CN119926417A